Evidence for antiviral effect of nitric oxide. Inhibition of herpes simplex virus type 1 replication. - Croen, K D (1993)
Nitric oxide (NO) has antimicrobial activity against a wide spectrum of infectious pathogens, but an antiviral effect has not been reported. The impact of NO, from endogenous and exogenous sources, on herpes simplex virus type 1 (HSV 1) replication was studied in vitro. HSV 1 replication in RAW 264.7 macrophages was reduced 1,806-fold in monolayers induced to make NO by activation with gamma IFN and LPS. A competitive and a noncompetitive inhibitor of nitric oxide synthetase substantially reduced the antiviral effect of activated RAW macrophages. S-nitroso-L-acetyl penicillamine (SNAP) is a donor of NO and was added to the media of infected monolayers to assess the antiviral properties of NO in the absence of gamma IFN and LPS. A single dose of S-nitroso-L-acetyl penicillamine 3 h after infection inhibited HSV 1 replication in Vero, HEp2, and RAW 264.7 cells in a dose-dependent manner. Neither virucidal nor cytocidal effects of NO were observed under conditions that inhibited HSV 1 replication. Nitric oxide had inhibitory effects, comparable to that of gamma IFN/LPS, on protein and DNA synthesis as well as on cell replication. This report demonstrates that, among its diverse properties, NO has an antiviral effect.